THE RELATION OF APICAL TUBERCULOSIS OF ADULTS TO THE FOCAL TUBERCULOSIS OF CHILDREN - Opie, Eugene L. (The Rockefeller University Press, 1917)
The age incidence of focal tuberculous lesions of the lungs demonstrates that they have their origin in most instances in childhood. Focal lesions which heal have been found at all ages after the 2nd year of life, but in more than half of all individuals these lesions are acquired between the ages of 10 and 18 years. In the period between 18 and 30 years at least 85 per cent of all individuals have 'acquired focal tuberculous lesions. The occurrence of tuberculous infection in the lungs, in regional lymphatic nodes, or in some other organs of the body such as the gastrointestinal tract and its lymphatic system, is nearly universal but doubtless a few individuals escape. That focal tuberculous lesions of the lung are occasionally acquired during adult life is shown by the slight increase in the proportion of those with these lesions as age increases from 18 years to old age. Apical lesions of the lung make their appearance in later childhood and occur with increasing frequency from adolescence to old age (50 per cent). After the 2nd year of life focal tuberculous lesions occurring in situations other than the apices of the lungs tend to heal and after the 10th year focal lesions are almost invariably encapsulated and latent or healed. Fatal tuberculosis after the 10th year is with few exceptions apical in origin. The apices are not only more susceptible to infection in later life but once infected afford less resistance to the extension of the lesion. The present series of cases has furnished opportunity to observe the character of the apical lesion in lungs of individuals previously infected with tuberculosis. With one exception the apical lesion (in eight instances) has pursued a chronic course and, encapsulated by fibrous tissue, has remained limited to the extreme apex of the lung. In one instance in a woman with advanced malignant disease chronic pulmonary tuberculosis has been progressive. Tuberculosis of the apices in those who have previously acquired a focal tuberculous lesion has pursued a chronic course and in most instances has remained latent or has completely healed. A very small group of instances of fatal pulmonary tuberculosis suggests that apical lesions in those who have not undergone previous infection may assume an unusually severe character. One instance of apical tuberculosis unaccompanied by focal lesions and followed by tuberculosis of the thoracic duct and disseminated miliary tuberculosis has been especially significant. Apical tuberculosis unaccompanied by evidence of preexisting tuberculosis may be accompanied by tuberculosis of the regional lymphatic nodes, whereas apical tuberculosis in an individual with a preexistent focal tuberculous lesion is not followed by tuberculosis of adjacent lymphatic nodes. It is well known that tuberculosis in previously uninfected animals is followed by tuberculosis of adjacent lymphatic nodes, whereas a second infection fails to implicate the regional lymphatic nodes. This relation has been well illustrated by the lungs of a monkey which acquired in confinement acute tuberculous pneumonia limited to the left lung; the lymphatic nodes on this side were greatly enlarged and caseous. The following observations indicate that apical tuberculosis of adults is not the result of infantile tuberculosis but is caused by subsequent infection: (a) Apical tuberculosis does not have its highest incidence, in accordance with common belief, in early adult life when focal infections acquired in childhood are relatively fresh and active but is more common in later life when the focal lesions of childhood have in most instances completely healed. It is noteworthy that most of these apical lesions of later life pursue a chronic course and are discovered at autopsy in individuals who have died from other causes. (b) The well characterized lesions of tuberculosis acquired in childhood and found in adults with apical lesions are almost invariably calcified and healed. The apical lesion is in most instances relatively fresh and caseous whereas the focal pulmonary lesion and associated lesions of regional lymphatic nodes exhibit no evidence of activity. (c) In a large proportion of instances of associated focal and apical tuberculosis the focal lesion is in one lung, whereas the apical lesion is limited to the opposite apex. This relation affords no support to the view that tuberculous lesions may be transmitted to the apex by way of the lymphatics.